Fluorescence multispectral imaging-based diagnostic system for atherosclerosis. Issue 1 (December 2016) - Ho, Cassandra; Horiuchi, Toshikatsu; Taniguchi, Hiroaki; Umetsu, Araya; Hagisawa, Kohsuke; Iwaya, Keiichi; Nakai, Kanji; Azmi, Amalina; Zulaziz, Natasha; Azhim, Azran; Shinomiya, Nariyoshi; Morimoto, Yuji
Abstract Background Composition of atherosclerotic arterial walls is rich in lipids such as cholesterol, unlike normal arterial walls. In this study, we aimed to utilize this difference to diagnose atherosclerosis via multispectral fluorescence imaging, which allows for identification of fluorescence originating from the substance in the arterial wall. Methods The inner surface of extracted arteries (rabbit abdominal aorta, human coronary artery) was illuminated by 405 nm excitation light and multispectral fluorescence images were obtained. Pathological examination of human coronary artery samples were carried out and thickness of arteries were calculated by measuring combined media and intima thickness. Results The fluorescence spectra in atherosclerotic sites were different from those in normal sites. Multiple regions of interest (ROI) were selected within each sample and a ratio between two fluorescence intensity differences (where each intensity difference is calculated between an identifier wavelength and a base wavelength) from each ROI was determined, allowing for discrimination of atherosclerotic sites. Fluorescence intensity and thickness of artery were found to be significantly correlated. Conclusions These results indicate that multispectral fluorescence imaging provides qualitative and quantitative evaluations of atherosclerosis and is therefore a viable method of diagnosing the disease.